Effect of in ovo injection of epigallocatechin-3 gallate and oleuropein on hatching, productive and physiological aspects of broiler chicks exposed to short heat stress - Al-Shammari, K. I. A.; Zamil, S. J. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
This study was aimed to investigate the influence of in ovo injection (IO) into air cell (AC) or yolk sac (YS) of epigallocatechin-3 gallate (EG) and oleuropein (OL) as antioxidants on hatching, physiological and productive performance of heat-stressed chicks. 840 fertile eggs were chosen for IO on 12th day of incubation. Eggs were divided into 7 groups within 4 replications each as follows: negative control (NC) without IO and other groups involved IO of 100 μl distilled water and 5 mg each of EG and OL in both AC and YS sites of egg. After hatching, chicks were exposed to heat stress for 24 h and raised for 42 d. Compared with NC, the results revealed that main effect of IO with EG and OL increased (p≤0.05) hatchability and decreased deformed chicks and serum levels of glucose, cholesterol, aspartate aminotransferase, corticosterone and heat shock protein 70 with enhancing feed efficiency, superoxide dismutase, glutathione peroxidase and thyroxine in serum or liver. High chick length and relative chick weight with low serum protein carbonyl and feed intake were recorded (p≤0.05) by EG. Low rectal temperature and heterophil to lymphocyte ratio with high body weight were recordered (p≤0.05) by OL. No mainly altered effects between both IO sites on most variables measured. However, there were significant influences among interactive treatments which related to in ovo injected substance in an injection site-dependent manner. It is concluded that improved hatchability, physiological and productive characteristics of heat-stressed chicks were achieved by IO of EG and OL.